2-Methoxy-1, 4-naphthoquinone regulated molecular alternation of Fusarium proliferatum revealed by high-dimensional biological data. Issue 24 (17th May 2022) - Yang, Jiajia; Xia, Xuewei; Guo, Meixia; Zhong, Li; Zhang, Xiaoyong; Duan, Xuewu; Liu, Jun; Huang, Riming
Abstract : Fungi Fusarium proliferatum and the toxins it produces are hazardous to agricultural plants, animals, and human health. The signaling pathways and biotargets of F. proliferatum triggered by MNQ were confirmed in this work. Abstract : Fungi Fusarium proliferatum and the toxins it produces are hazardous to agricultural plants, animals, and human health. However, there is a lack of more effective and environment-friendly natural anti- F. proliferatum agents. In the search for natural anti-fungal agents, we found that naturally originated 2-methoxy-1, 4-naphthoquinone (MNQ) with a minimal inhibitory dose of 8.0 mg L −1 possessed a potential inhibitory effect on F. proliferatum . The results of transcriptomic, proteomic, and metabolomic reveal a total of 1314 differential expression genes (DEGs, 873 up-regulated and 441 down-regulated), 259 differential expression proteins (DEPs, 104 up-regulated and 155 down-regulated), and 86 differential accumulation metabolites (DAMs, 49 up-regulated and 37 down-regulated) in MNQ-induced F. proliferatum . Further, the correlation analysis of transcriptomic, proteomic, and metabolomic indicated that these DEGs, DEPs, and DAMs were co-mapped in the pathways of glyoxylate and dicarboxylate metabolism, glycine, serine, and threonine metabolism, and pyruvate metabolism that linked to the TCA cycle. Furthermore, the key DEGs of the significantly co-mapped pathways were verified with qPCR analysis, which was related to the permeability of the cell membrane of F. proliferatum . Thus, these findings will provide fundamental scientific data on the molecular shifts of MNQ-induced F. proliferatum .